Antifungal activity of microbial secondary metabolites. - Jeffrey J Coleman; Suman Ghosh; Ikechukwu Okoli; Eleftherios Mylonakis (PLoS ONE, 2011)
Secondary metabolites are well known for their ability to impede other microorganisms. Reanalysis of a screen of natural products using the Caenorhabditis elegans-Candida albicans infection model identified twelve microbial secondary metabolites capable of conferring an increase in survival to infected nematodes. In this screen, the two compound treatments conferring the highest survival rates were members of the epipolythiodioxopiperazine (ETP) family of fungal secondary metabolites, acetylgliotoxin and a derivative of hyalodendrin. The abundance of fungal secondary metabolites indentified in this screen prompted further studies investigating the interaction between opportunistic pathogenic fungi and Aspergillus fumigatus, because of the ability of the fungus to produce a plethora of secondary metabolites, including the well studied ETP gliotoxin. We found that cell-free supernatant of A. fumigatus was able to inhibit the growth of Candida albicans through the production of a secreted product. Comparative studies between a wild-type and an A. fumigatus ΔgliP strain unable to synthesize gliotoxin demonstrate that this secondary metabolite is the major factor responsible for the inhibition. Although toxic to organisms, gliotoxin conferred an increase in survival to C. albicans-infected C. elegans in a dose dependent manner. As A. fumigatus produces gliotoxin in vivo, we propose that in addition to being a virulence factor, gliotoxin may also provide an advantage to A. fumigatus when infecting a host that harbors other opportunistic fungi.